A Renovação Carismática Católica na condição Pós-Moderna e na hipermodernidade: as características dos seus sujeitos ante as novas tendências dos tempos atuais - Scherer, Karine Pagliosa (2014)
The thesis focuses on the subject of Catholic Charismatic Renewal (CCR) in current times, particularly in the Brazilian context. Working theoretically, it seeks to define the subject, focuses on the distinction between the individual, the, subject and the actor and their characteristics in post and hypermodernity. It then points out the Movement in which this subject is born, shaped and acts, describing the CCR, its origins, expansion and peculiarities within the Catholic Church. This accomplished, it goes in search of the characteristics of the subjects of the CCR. Living in the postmodern condition or hypermodernity which values the culture of consumption and pleasure, while at the same time causes distress, fragmentation, disorientation, the Catholic Charismatic Renewal subject acquires individual happiness that gives him unity, emotional security, comfort, anchoring and communicative warmth. It searches and acquires an intimate religiousness, focused on family life, on fervor in individual and community prayer and ritual worship. Social and collective questions in a world of great injustice give way to concerns of individual order. It reinforces the moralizing and conservative values in the field of behavior. Through its intense work of lay missionary, countless sectors of the Catholic Church in Brazil and the world show gratitude and unconditional support to their charismatic believers because they are valuable actors to renew the Church s herd which, in recent times, has been suffering of a deep demographic crisis